CYTOTOXICITY AND HAEMOLYTIC PROPERTIES FROM RHIZOPHORA MUCRONATA MANGROVE PLANT EXTRACT - R R San Chitta raj, Dr. Abirami Arthanari (Chelonian Research Foundation, 2023)
INTRODUCTION Mangrove plants have long been recognized for their potential pharmacological properties, yet comprehensive studies on their cytotoxic and hemolytic effects are limited. In this study, we aimed to investigate the cytotoxicity and hemolytic properties of an extract obtained from Rhizophora Mucronata, a prominent mangrove species. The research was conducted to assess the safety and potential therapeutic applications of this plant extract. MATERIALS AND METHODS Fresh leaves and stems of Rhizophora Mucronata were collected from a designated mangrove habitat Plant material was washed, air-dried, and ground into a fine powder.Extraction was performed using [Solvent], and the resulting crude extract was obtained through maceration. RESULTS The chemical composition of the Rhizophora Mucronata extract was analysed using various spectroscopic and chromatographic techniques, revealing the presence of bioactive compounds, including phenolic compounds, flavonoids, and tannins. These compounds may contribute to the observed cytotoxic and hemolytic effects and warrant further investigation for potential therapeutic applications. CONCLUSION The Rhizophora Mucronata mangrove plant extract demonstrates promising cytotoxic activity against cancer cells while exhibiting minimal hemolytic properties. This suggests its potential as a source for the development of novel anticancer agents with improved safety profiles. Further research is needed to elucidate the precise mechanisms of action and to isolate and characterise the bioactive compounds responsible for these effects. KEYWORDS: Rhizophora Mucronata ,Mangrove plant extract,Cytotoxicity,Hemolytic properties,Anticancer activity,Cell viability ,Hemolysis ,Bioactive compounds